Benefits and challenges of the internet of things in aquaculture production: a literature review - María Claudia Bonfante Rodríguez; Cielo Ester Marriaga González; Eivy Daniel Coneo Almanza; Cristian González Rodríguez; Jose Ángel Regino-Vergara; Alexis López-Padilla (Frontiers in Sustainable Food Systems)
To advance research that enables the integration of Industry 4.0 technologies and enhances competitiveness in the aquaculture sector, it is crucial to review the existing literature on the applications, architecture, and challenges of the Internet of Things (IoT) in production processes. This study employs a structured five-phase methodology, which includes the formulation of three research questions, a targeted search for relevant information using key descriptors in the Dimensions database, the establishment of inclusion and exclusion criteria, the assessment of the relevance and quality of selected contributions, and the synthesis of findings. The analysis identified key factors affecting production, as well as the architectural components essential for monitoring water quality. The results indicate that the IoT presents a significant opportunity for growth in the sector. Nevertheless, several challenges remain, including limited access to and design of devices, inadequate connectivity for data transmission, data storage constraints, high energy consumption, sensor calibration issues, and poor-quality sensory data that can impede effective decision-making. The study concludes that addressing this technological gap will require the development of low-cost, yet highly efficient, hardware and software solutions tailored to the specific needs of the aquaculture industry.